Mengimajinasikan Kembali Masalah Rasisme: Sebuah Respons Injili terhadap Rasisme - Hendra Winarjo (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
This article aims to re-imagine and offer an evangelical response to the problem of racism that is not dichotomous, but holistic, where racism is understood both as an individual and structural sin, leading to a balance between racial reconciliation and racial justice that needs to be consistently practiced. This research indicates that evangelicals generally do not yet have a holistic imagination to understand racism. Hence efforts to fight this persisting problem are still one-sidedly inclined toward racial reconciliation. For this purpose, this article begins by analyzing the common yet problematic understanding and response by some evangelicals who emphasize racism as only an individual sin and racial reconciliation as a solution. The next step is to describe the importance of imagination, namely the capacity to conceptualize the problem of racism in its entirety by involving sensitivity to racist situations, interpretation of Scripture with virtues, and introspection of our position toward racism—all of which are used to understand the dual nature of racism and response against it. In the end, as I demonstrate that racism is both an individual and structural sin, evangelical churches thus need to strike a balance between racial reconciliation and racial justice if they want to handle the problem of racism well.